Reserve Accumulation and International Monetary Stability : Supplementary Information. (Policy Papers; Policy Paper, 2010)
Reform package. Comprehensive reform of Fund governance-encompassing quotas, ministerial engagement and oversight, the size and composition of the Executive Board, voting rules, management selection, and staff diversity-is essential to enhancing the Fund's long-term legitimacy and effectiveness. Although the elements of such a reform are being discussed sequentially, and some could be taken up sooner, most will need to be decided as a package, given the linkages and trade-offs.